1998
DOI: 10.1037/0096-1523.24.5.1342
|View full text |Cite
|
Sign up to set email alerts
|

Attentional control during visual search: The effect of irrelevant singletons.

Abstract: Four experiments investigated whether a highly salient color singleton can be ignored during serial search. Observers searched for a target letter among nontarget letters and were instructed to ignore an irrelevant, highly salient color singleton that was either compatible or incompatible with the response to the target letter. The results indicate that it was possible to prevent attentional capture by the irrelevant singleton only when both the target and the distractor color were known. When either the color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
216
5
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(248 citation statements)
references
References 39 publications
26
216
5
1
Order By: Relevance
“…For instance, regarding the reflexive attention aspect: In Rauschenberger's (2003b) study, when participants were set for new object onset, large luminance changes might be considered to be highly salient, so they captured attention, whereas small luminance changes might be considered to be relatively low salient, so they failed to capture attention. Regarding the voluntary attention aspect, in Theeuwes and Burger's (1998) study, the congruency effect associated with a salient but to-be-ignored color distractor was eliminated only when participants were fully informed about the colors of the target and the distractor. Recent progress in physiological studies may shed light on the neural mechanism.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, regarding the reflexive attention aspect: In Rauschenberger's (2003b) study, when participants were set for new object onset, large luminance changes might be considered to be highly salient, so they captured attention, whereas small luminance changes might be considered to be relatively low salient, so they failed to capture attention. Regarding the voluntary attention aspect, in Theeuwes and Burger's (1998) study, the congruency effect associated with a salient but to-be-ignored color distractor was eliminated only when participants were fully informed about the colors of the target and the distractor. Recent progress in physiological studies may shed light on the neural mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…Although there has been relatively little direct evidence supporting attentional capture by salient static stimuli, some recent studies have demonstrated capture effects by using indirect methods that reasonably rule out possible top-down influences (Horstmann, 2002;Theeuwes & Burger, 1998;Theeuwes & Godijn, 2002). For instance, Theeuwes, Atchley, and Kramer (2000) found that a color singleton distractor indeed interfered with the search for a shape singleton target when the distractor preceded the target by 100 msec or less, suggesting that attention might be initially drawn to the distractor position and then swiftly disengaged.…”
mentioning
confidence: 99%
“…A number of behavioral and electrophysiological findings in the literature are in line with this conclusion. For example, it has been shown that items at nontarget locations attract attention in visual search to the extent that they bear features of the searched-for set (Kim and Cave, 1995;Shui-I and Sperling, 1996;Theeuwes and Burger, 1998;Woodman and Luck, 1999;Arnott et al, 2001;Theeuwes et al, 2001). In particular, Folk and colleagues (Folk et al, 1992(Folk et al, , 1994(Folk et al, , 2002Folk and Remington, 1998) and others (Yantis and Egeth, 1999) have shown that distractors matching the attentional set are highly effective at capturing attention when attention is not already strongly focused on a different location.…”
Section: Discussionmentioning
confidence: 99%
“…To further support the claim that both cues captured attention, we investigated whether cued distractor identities interfered with responses to the target, following the identity intrusion method introduced by Theeuwes (1996; see also Theeuwes & Burger, 1998). If attention is shifted to the location of the cue, the assumption is that the identity of the object at that position will be preferentially processed (e.g., Kramer & Jacobson, 1991).…”
Section: Methodsmentioning
confidence: 99%